The economisation of climate change : how the G20, the OECD and the IMF address fossil fuel subsidies and climate finance - Skovgaard, Jakob, 1977- (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2021)
"The year 2019 saw the emergence of an unlikely duo consisting of the Managing Director of the International Monetary Fund (IMF) Christine Lagarde1 and broadcaster and environmentalist Sir David Attenborough. They discussed the relationship between nature and the economy in a panel session, a podcast and an article (Attenborough and Lagarde, 2019, Atttenborough and Lagarde, 2019). In the latter, they stated 'We must treat the natural world as we would the economic world ... This is something economists can appreciate - the importance of minimizing waste, taking advantage of efficiencies, and accurately reflecting costs in prices, including costs imposed on our entire shared resource, the environment'. Elsewhere the same year, Lagarde also stated the importance of nature and of the existential threat of climate change and called for carbon pricing and fossil fuel subsidy reform as solutions to the climate crisis (Lagarde and Gaspar, 2019). This was notable coming from the Managing Director of an international institution focused on economic issues and criticised for ignoring other issues than economic growth and stability. The statement highlighted a wider trend of climate change being addressed within institutions concerned with economic issues"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Climatic changes -- Economic aspects; Environmental policy -- Economic aspects